Comparative in vitro study of intracanal Enterococcus faecalis reduction using photosensitizers in aPDT - Maria Cleide Azevedo Braz; André Hayato Saguchi; Eduardo Akisue; Adriana de Oliveira Lira; Sidnea Aparecida Freitas Paiva; Aldo Brugnera Junior; Mary Caroline Skelton Macedo; André Luiz da Costa Michelotto; Ângela Toshie Araki (Universidade Estadual de Campinas, 2021)
Aim: To compare Enterococcus faecalis reduction after antimicrobial photodynamic therapy (aPDT) used with methylene blue, toluidine blue, tannin, and curcumin as photosensitizers, an adjunct to endodontic chemomechanical preparation (CMP) in root canals of human teeth. Methods: A total of 120 single-rooted teeth were divided into 6 groups (n  =  20): G1- CMP and 2.5% sodium hypochlorite (NaOCl); G2- CMP and saline solution; G3- CMP, 2.5% NaOCl, and aPDT with 0.005% methylene blue; G4- CMP, 2.5% NaOCl, and aPDT with 0.005% toluidine blue; G5- CMP, 2.5% NaOCl, and aPDT with 0.005% tannin; and G6- CMP, 2.5% NaOCl, and aPDT with 0.005% curcumin. A portable semiconductor laser was used (660  nm, 100  mW, 1.8  J, 180s) in groups 1, 2, 3, 4, 5, and a blue LED light-curing (420-480  nm, 1200 mV/cm2 ) in G6. For all groups, a 5 min pre-irradiation time was applied. Samples were collected before (initial collection), immediately after (intermediate collection) and 7 days after CMP (final collection) for colony-forming unit (CFU) counting. The Kruskal-Wallis test and analysis of variance (ANOVA) were performed (p < 0.05; 95% confidence interval). Results: In between-group comparisons, there was no significant difference observed in the number of CFUs at the initial (p >< 0.001) and final collections (p >< 0.001) for G2 and G3. In within-group comparisons, the number of CFUs showed a decreasing trend in G4 (p = 0.007) and G5 (p = 0.001). Conclusion: Photosensitizers promoted E. faecalis reduction, with better results for tannin and curcumin. Alternative photosensitizers should be the focus of further studies.>< 0.05; 95% confidence interval). Results: In between-group comparisons, there was no significant difference observed in the number of CFUs at the initial (p < 0.001) and final collections (p >< 0.001) for G2 and G3. In within-group comparisons, the number of CFUs showed a decreasing trend in G4 (p = 0.007) and G5 (p = 0.001). Conclusion: Photosensitizers promoted E. faecalis reduction, with better results for tannin and curcumin. Alternative photosensitizers should be the focus of further studies.><  0.001) and final collections (p < 0.001) for G2 and G3. In within-group comparisons, the number of CFUs showed a decreasing trend in G4 (p = 0.007) and G5 (p = 0.001). Conclusion: Photosensitizers promoted E. faecalis reduction, with better results for tannin and curcumin. Alternative photosensitizers should be the focus of further studies>< 0.001) for G2 and G3. In within-group comparisons, the number of CFUs showed a decreasing trend in G4 (p = 0.007) and G5 (p = 0.001). Conclusion: Photosensitizers promoted E. faecalis reduction, with better results for tannin and curcumin. Alternative photosensitizers should be the focus of further studies.